2007
DOI: 10.1200/jco.2007.12.2705
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Treatment Outcome With Adjuvant Tamoxifen Relative to Patient CYP2D6 and CYP2C19 Genotypes

Abstract: Because genetically determined, impaired tamoxifen metabolism results in worse treatment outcomes, genotyping for CYP2D6 alleles *4, *5, *10, and *41 can identify patients who will have little benefit from adjuvant tamoxifen therapy. In addition to functional CYP2D6 alleles, the CYP2C19 *17 variant identifies patients likely to benefit from tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
342
6
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 416 publications
(373 citation statements)
references
References 31 publications
18
342
6
7
Order By: Relevance
“…Although the present work has some limitations (the retrospective bias selection of patients, the sample size, the possible use of co-administered inhibitors and the infrequency of the CYP2D6 variants in the European population) our results clearly show a significant association between an absent or reduced enzyme function-homozygous or compound heterozygous for CYP2D6 alleles *4, *5, and *41-and worse disease-free survival. Benefits in event-free survival were similar to those found by Schroth and Goetz [14,15]. The fact that CYP2D6 poorer metabolizers have a worse clinical outcome than better metabolizers could be related to a reduced tamoxifen metabolism and lower endoxifen levels in the former; if we assume that a certain level of endoxifen is sufficient and necessary for tamoxifen efficacy, this level would not be reached by neither any CYP2D6 poor metabolizer nor by some of the patients with an intermediate metabolizer genotype.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Although the present work has some limitations (the retrospective bias selection of patients, the sample size, the possible use of co-administered inhibitors and the infrequency of the CYP2D6 variants in the European population) our results clearly show a significant association between an absent or reduced enzyme function-homozygous or compound heterozygous for CYP2D6 alleles *4, *5, and *41-and worse disease-free survival. Benefits in event-free survival were similar to those found by Schroth and Goetz [14,15]. The fact that CYP2D6 poorer metabolizers have a worse clinical outcome than better metabolizers could be related to a reduced tamoxifen metabolism and lower endoxifen levels in the former; if we assume that a certain level of endoxifen is sufficient and necessary for tamoxifen efficacy, this level would not be reached by neither any CYP2D6 poor metabolizer nor by some of the patients with an intermediate metabolizer genotype.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have evaluated the association between CYP2D6 genotype and clinical outcomes in women treated with adjuvant tamoxifen [11][12][13][14][15]. Two studies [14,15] retrospectively enrolled relatively homogeneous populations of patients who were estrogen-receptor positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that CYP2C19 may be a risk factor per se, or that it can be important for tamoxifen response and is further enhanced by its association with CYP2D6. 19 Our data do not confirm this observation, possibly because of the relatively low number of subjects with these SNPs variants. It has also been reported that SULT1A1 may influence tamoxifen metabolites' concentration.…”
Section: Serrano Et Alcontrasting
confidence: 66%
“…18,19 Moreover, the clearance, mediated by sulfotransferase (SULT)1A1 and UDP-glucuronosyltransferase (UGT) 2B15 and UGT1A4, may regulate the metabolite concentration as reported by Nowell et al 20 So far the main focus of research has been on CYP2D6 PMs, although activity enhancement may also have clinical relevance. Genotypically, PM patients or patients receiving CYP2D6-inhibiting drugs have reduced plasma concentrations of endoxifen.…”
Section: Introductionmentioning
confidence: 99%